Peningkatan Efektivitas Komunikasi Vertikal: Pendekatan Analisis Terhadap Dinamika Interaksi di Perusahaan PT Pos Medan - Harmen, Hilma; Wati, Aprina; Hutapea, Marsela Natalie; Tambunan, Indah Permatasari; Aulia, Dina; Samuel, Zsevta; Hasibuan, Najwa Aulia Putri (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Vertical communication is the process of exchanging information, ideas, or instructions that occurs between various hierarchical levels or strata in an organization. This research aims to analyze and improve the effectiveness of vertical communication in the PT Pos Medan company environment through an analytical approach to the dynamics of interaction between hierarchical levels. Effective vertical communication is essential in ensuring the smooth flow of information and coordination within the organization. In this research, we use an analytical approach to understand communication patterns between management levels, identify factors inhibiting communication, and evaluate strategies that can improve collaboration and coordination between organizational levels.